2023
DOI: 10.1111/liv.15639
|View full text |Cite
|
Sign up to set email alerts
|

Accumulating awareness on the clinical significance and relevance of frailty in cirrhosis: Time to dig deeper into mechanistic basis!

Abstract: Given the multifactorial nature and complex pathogenesis in relation to liver cirrhosis, it is justified to stratify progression risk and to prognosticate mortality in terms of various pathological pertubations alongside laboratory markers. In other words, conventional scoring systems, such as the model for end-stage liver disease (MELD) or Child-Turcotte-Pugh (CTP) classification, may fail to capture specific derangements across multiple physiological pillars, which include but not limited to musculoskeletal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 100 publications
(203 reference statements)
0
1
0
Order By: Relevance
“…These findings also suggested that cirrhotic patients with frailty may be at high risk for receiving invasive treatments, which may be another potential reason for the poor long-term clinical outcomes of these patients [ 45 ]. Pathophysiologically, frailty has been related to upregulated inflammatory response, impaired systemic immune dysfunction, and gut microbiota disorder [ 46 48 ], which may also partly explain the association between frailty and poor TFS in patients with cirrhosis. Studies are warranted to determine the molecular pathways involved.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also suggested that cirrhotic patients with frailty may be at high risk for receiving invasive treatments, which may be another potential reason for the poor long-term clinical outcomes of these patients [ 45 ]. Pathophysiologically, frailty has been related to upregulated inflammatory response, impaired systemic immune dysfunction, and gut microbiota disorder [ 46 48 ], which may also partly explain the association between frailty and poor TFS in patients with cirrhosis. Studies are warranted to determine the molecular pathways involved.…”
Section: Discussionmentioning
confidence: 99%